The Appeal of Risky Assets - Anno Stolper (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2010)
A fund's performance is usually compared to the performance of an index or other funds. If a fund trails the benchmark, the fund manager is often replaced. We argue that this may lead to excessive risk-taking if fund managers differ in ability and have the opportunity to take excessive risk. To match the benchmark, fund managers may increase the risk of their portfolio even if this decreases the expected return on the portfolio.
urn:nbn:de:bvb:19-epub-11878-5
Keywords: G01; G11; G23; 330; Benchmarking; risk taking; Investmentfonds; Führungskräfte; Anlageverhalten; Risikofreude; Performance-Messung; Benchmarking; Ökonomischer Anreiz; Theorie